Selenium enriched eggs is more effective to increase serum glutathione peroxidase and decrease F2-isoprostane level of excessive physical training-induced rats (Rattus norvegicus) than ordinary eggs - Felix Kusmana; I Gusti Made Aman; Gde Ngurah Indraguna Pinatih (Fakultas Kedokteran Universitas Udayana, 2021)
Abstract Background: Exercise maintains health and prevent aging. However, excessive exercise causes overtraining syndrome. Selenium supplementation may increase cellular antioxidant activity, such as glutathione peroxidase (GPx), thioredoxin reductase (TRx), and selenoprotein P. This study aimed to prove that selenium-enriched eggs is more effective to increase serum glutathione peroxidase and decrease F2-isoprostane level of excessive physical training-induced rats (Rattus norvegicus) than ordinary eggs.Methods: This experimental study used randomized pretest-posttest control group design. Subjects were 16 male Wistar rats, 16 weeks old, healthy, weighing 150-160 grams. Subjects were divided randomly into 2 groups (n=8), one group was treated with excessive physical training and 6.48 grams of ordinary eggs, and another group was treated with excessive physical training and 6.48 grams of selenium-enriched eggs for 14 days. Results: Post-test analysis showed that the mean of glutathione peroxidase level in the group given ordinary eggs was 45.90±8.11 mIU/mL, while the group given selenium-enriched eggs was 72.61±7.40 mIU/mL (p= 0.001). In addition, the mean of F2-Isoprostane level in the group given ordinary eggs was 6.37±1.34 ng/ml and the group given selenium-enriched eggs was 3.39±0.77 ng/ml (p= 0,001). Analysis of paired sample t-test revealed that in both groups, glutathione peroxidase levels were increase while F2-isoprostane levels were decrease. Conclusion: This study suggested that selenium-enriched eggs is more effective to increase serum glutathione peroxidase and decrease F2-isoprostane level of excessive physical training-induced rats (Rattus norvegicus) than ordinary eggs. Key words: excessive physical training, F2-isoprostane, glutathione peroxidase, selenium-enriched eggs, Wistar rat.